The Rising Trend of Drug Addiction and Its Impacts on Youth's Mental Health - Somia Shabbir; Alishba Riaz; Arsalan Arif; Bibi Zainab; Farooq Shah; Mehreen Faiza (Research Journal of Psychology, 2025)
The rising trend of drug addiction among youth has become a major public health concern, significantly impacting mental health. The relationship of drug addiction and mental health disorders among university students of Lahore and Karachi was quantitatively studied. A structured survey of 150 university students from both cities was done and a statistical analysis was carried out to measure the incidence and severity of addiction related psychological distress. Likert five point scale was used as instrument in this study. Descriptive and inferential statistics used to generate the results from collected data. Across the board, positive correlation between drug use and reduced mental health with increased drug use corresponding with more anxiety and depression symptoms. The paper underlines the necessity for preventive measures, awareness programs and policy interventions aimed at substance abuse and its psychological implications among youth at urban settings.